OP277 Rapid Development Of An Evaluation Framework: Capturing The Impact Of COVID-19 Activities By A Health Technology Assessment Body. (December 2021) - Elston, Lauren; Hughes, Sophie; Myles, Susan
Abstract : Introduction: Health Technology Wales (HTW) is committed to evaluating the impact of our work. In March 2020, HTW directed efforts to support Welsh Government and health and social care providers in response to the COVID-19 pandemic. We adapted the HTW evaluation framework to specifically capture the impact of our additional COVID-19 work. Here we analyze data collected since the framework was implemented. Methods: Both formal and informal feedback was analyzed. Formal feedback was obtained through the HTW Impact Questionnaire, which was developed to support more formalized data capture for all HTW workstreams and to facilitate feedback from all stakeholder groups. It was piloted with a targeted list of individuals and responses were received for COVID-19 work. Informal feedback included feedback received via email or through word of mouth. Results: HTW COVID-19 products to date include Topic Exploration Reports, rapid evidence summaries and an Evidence Appraisal Report (EAR) on COVID-19 diagnostic tests (molecular and antibody tests). Stakeholders were positive about these outputs, describing them as valuable and informative. Reported impacts included informing policy and decision making, reducing duplication of efforts and helping to target development. The EAR received national and international focus, leading to HTW involvement in the European Network for Health Technology Assessment (EUnetHTA) COVID-19 reviews. Survey participants who gave feedback on COVID-19 activities included two members of Health Technology Assessment organizations, a health board representative and an industry representative; all agreed that HTW's COVID-19 work was useful, that the methods were reliable and robust and that HTW is responsive. All participants also felt that HTW's COVID-19 work had a positive impact in the wider health and social care context. Conclusions: HTW was able to respond rapidly to the COVID-19 pandemic and adapt current evaluation practices to capture the impact of COVID-19 work. We will continue to evaluate our COVID-19 activities. Future work will involve following up on the developing impact of our COVID-19 work and expanding our methods for data capture, for example conducting stakeholder interviews.